The Prevalence of Pelvic Organ Prolapse in Coastal Community from Riau Province - Edy Fakhrizal; Ruza Prima Rustam; Sri Wahyu Maryuni (Nusantara Science and Technology Proceedings, 2022)
A woman’s quality of life is determined by their physical, psychosocial, and sexual function. These functions are impaired with pelvic organ prolapse (POP), causing a vast burden, individually and globally. With its geographic location, the coastal community may have difficulties in seeking medical attention as the health care facilities provided are limited. To date, no study has been conducted to identify the POP prevalence rate among the coastal community of Riau Province as one of the coastal areas in Indonesia. This study aims to help in determining problems caused by POP, eventually designing effective prevention and treatment strategies to be proposed to health policymakers. This is a quantitative study with all reproductive ages (20 – 44 years old) and >44 years old women in 4 coastal areas in Riau Province (Bengkalis, Dumai, Siak, and Pekanbaru) as the key population. The validated Pelvic Floor Distress Inventory (PFDI) questionnaire in Bahasa Indonesia is used to assess the POP prevalence rate. Out of 343 participants, 204 (63,75%) had POP. The highest POP incidence rate was found in Bengkalis, with a total of 61 (30%) participants with POP. Dumai, Siak, and Pekanbaru had the incidence rate of 59 (29%), 59 (29%), and 25 (12%) consequently. Based on this study, due to the high prevalence of POP, the authors agreed that effective prevention and treatment strategies are needed to prevent the severity and further development of POP.